2014
DOI: 10.3389/fonc.2014.00139
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Selective Induction of Apoptosis by Leczyme

Abstract: Sialic acid-binding lectin (SBL) is a multi-functional protein that is isolated from oocytes of Rana catesbeiana. It has both lectin and ribonuclease (enzyme) properties, and therefore is called leczyme. We examined the anti-tumor effects of SBL and discovered that SBL has potential as a new type of anti-cancer drug. SBL causes a cancer-selective induction of apoptosis by multiple signaling pathways whereby RNA is its target. It is suggested that the mitochondrial pathway and endoplasmic reticulum stress-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
1
10
0
1
Order By: Relevance
“…Cell apoptosis, proliferation and differentiation are all basic, vital functions of cells, which are closely associated; imbalances in these functions have been associated with tumor development (16,17). In general, apoptosis has a negative regulatory role in cancer cells and may inhibit tumor growth (18). Consistent with the increase in apoptosis observed in the present study, inhibition of Bcl-2 expression in NHERF1 knockdown cells was detected.…”
Section: Discussionsupporting
confidence: 80%
“…Cell apoptosis, proliferation and differentiation are all basic, vital functions of cells, which are closely associated; imbalances in these functions have been associated with tumor development (16,17). In general, apoptosis has a negative regulatory role in cancer cells and may inhibit tumor growth (18). Consistent with the increase in apoptosis observed in the present study, inhibition of Bcl-2 expression in NHERF1 knockdown cells was detected.…”
Section: Discussionsupporting
confidence: 80%
“…SBL induces cell death in various types of human cancer cells ( 7 ). To examine the antitumor effect of SBL on breast cancer cells, we used one estrogen-positive cell line (MCF-7) and two estrogen-negative cell lines (SK-BR-3 and MDA-MB231) for a cell viability assay.…”
Section: Resultsmentioning
confidence: 99%
“…SBL also exhibits a prominent antitumor effect on many types of cancer and tumor cells, such as breast, cervical, oral cancer, glioblastoma, and T-cell leukemia, but not normal cells, such as keratinocytes, fibroblasts, and lymphocytes ( 3 6 ). Moreover, the treatment of cancer cells with SBL ultimately leads to cell death ( 7 ). In mice with ascites tumor cells, the injection of SBL inhibits tumor growth and prolongs the life span, and sialidase protects cancer cells from SBL toxicity ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…79 Sialic acid-binding lectin (SBL) is a multi-functional protein that is isolated from oocytes of Rana catesbeiana which displays caspase 3 dependent killing of cancer cells. 80 Selective treatment of cell lines with SBL revealed that SBL induces cell death on estrogen receptor (ER)-positive breast tumors but not on ER-negative breast tumors. 81 The anti-tumor effect of SBLtreated ER-positive breast tumors is accompanied by the downregulation of ER and Bcl-2.…”
Section: Antibodies As Mimics Of Lectinsmentioning
confidence: 99%